The Effectiveness of Mind Mapping Method to Improve Understanding of Arabic Vocabulary - Mardi Hadi; Hendar Ibnu Hajar; Tufailah Ali; Imam Asrofi (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
Research is a study of the elements that form poetry. In analyzing poetry, attention is usually paid to the relationship between lyrics in verses, the relationship between verses, intrinsic elements in verses, and the message conveyed by a poet, and includes the style of language used and the meaning contained in a poem. This study aims to analyze the aspects of lexical semantics and grammatical semantics in the poem by Imam Asy-Syafi'i entitled